2014
DOI: 10.1002/mbo3.173
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cyanobacterial microcystin synthetase (mcy) E gene transcript levels, mcy E gene copies, and biomass as indicators of microcystin risk under laboratory and field conditions

Abstract: Increased incidences of mixed assemblages of microcystin-producing and nonproducing cyanobacterial strains in freshwater bodies necessitate development of reliable proxies for cyanotoxin risk assessment. Detection of microcystin biosynthetic genes in water blooms of cyanobacteria is generally indicative of the presence of potentially toxic cyanobacterial strains. Although much effort has been devoted toward elucidating the microcystin biosynthesis mechanisms in many cyanobacteria genera, little is known about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 71 publications
2
31
0
Order By: Relevance
“…Although no microcystin measurements were performed in this study, it has been shown that expression of microcystin synthesis genes correlates with levels of microcystin in some studies (Kuniyoshi et al, 2013;Pimentel & Giani, 2014;Sevilla et al, 2008), while other studies could not show this connection (Kaebernick et al, 2000;Ngwa et al, 2014;Sipari, Rantala-Ylinen, Jokela, Oksanen, & Sivonen, 2010;Wood et al, 2011). Microcystin measurements can also be misleading because the lag phase between transcription and actual microcystin formation remains unknown and because protein-bound microcystin might be missed (Zilliges et al, 2011).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Although no microcystin measurements were performed in this study, it has been shown that expression of microcystin synthesis genes correlates with levels of microcystin in some studies (Kuniyoshi et al, 2013;Pimentel & Giani, 2014;Sevilla et al, 2008), while other studies could not show this connection (Kaebernick et al, 2000;Ngwa et al, 2014;Sipari, Rantala-Ylinen, Jokela, Oksanen, & Sivonen, 2010;Wood et al, 2011). Microcystin measurements can also be misleading because the lag phase between transcription and actual microcystin formation remains unknown and because protein-bound microcystin might be missed (Zilliges et al, 2011).…”
Section: Discussionmentioning
confidence: 80%
“…Reverse-transcriptase quantitative polymerase chain reaction (RT-qPCR) has been used to understand the impact of nutritional and other factors on the expression of microcystin genes. For instance, the influence of micro-and macronutrients on mcyD expression was investigated (Kuniyoshi, Sevilla, Bes, Fillat, & Peleato, 2013;Pimentel & Giani, 2014;Sevilla et al, 2008Sevilla et al, , 2010, and the effect of high light stress as well as co-occurring cyanobacteria and cell concentration on mcyE expression was studied (Ngwa, Madramootoo, & Jabaji, 2014;Tran, Bernard, Ammar, Chaouch, & Comte, 2013;Wood et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As already mentioned, this targeted gene belong to the gene clusters involved in the biosynthesis of MCs (mcyA-E), which are widely used due to their usefulness for the early detection of potentially toxic cells even when the toxin concentrations are too low to be detected [21]. Due to lack of universal primers (e.g., [26,63]), for this study, the mcyE gene was chosen out of the other potentially usable mcy genes because of its reliable biomarker character for detection of MC-producing cyanoprokaryotes and its strong indicator properties for identifying of potential risk from MCs, even in water bodies comprising mixed assemblages of toxic and non-toxic cyanobacteria (e.g., [64][65][66][67][68][69]). Moreover, the similarity between MCs and NODs biosynthesis pathways [22,23] enabled the development of molecular detection methods for identifying all the main producers of MCs and NODs in environmental samples based on mcyE-gene and the orthologous nodularin synthetase gene F (ndaF) sequences with specific detection of the mcyE/ndaF gene pairs [65,70,71].…”
Section: Molecular Studiesmentioning
confidence: 99%
“…During the bloom, two potent cyanotoxins, cylindrospermopsin and saxitoxin, were observed, along with species with the genetic capacity to produce microcystins (Al-Tebrineh et al, 2011). There is an evident difficulty in correlating many environmental parameters with cyanobacterial community composition, toxicity or toxigenicity across such studies (Rinta-Kanto et al, 2009;Al-Tebrineh et al, 2011;Otten et al, 2012;Lee et al, 2014;Ngwa et al, 2014). In part, this lack of correlation can be attributed to genomic variability among closely related strains (Humbert et al, 2013;Sinha et al, 2014), giving rise to differing growth optima and potential to produce a myriad of toxic and non-toxic metabolites (Humbert et al, 2013), changes in the genome copy number throughout the growth phase (Griese et al, 2011) and uncertainty regarding the control of regulatory systems that direct the expression of toxic metabolites (Kaebernick et al, 2000;Alexova et al, 2011;Carneiro et al, 2013;Neilan et al, 2013;Rzymski and Poniedziałek, 2014;Makower et al, 2015).…”
Section: Introductionmentioning
confidence: 99%